Sanqi Qushi Granule Alleviates Proteinuria and Podocyte Damage in NS Rat: A Network Pharmacology Study and in vivo Experimental Validation - Wang L; Liu H; Wang Y; Hong X; Huang X; Han M; Wang D; Shan W; Li P; Gu H; Liu B; Bao K (Dove Medical Press, 2023)
Lijuan Wang,1,* Huoliang Liu,2,* Yi Wang,1 XiaoFan Hong,1 Xiaoyan Huang,1,3,4 Miaoru Han,1 Dan Wang,1 Wenjun Shan,1 Ping Li,1,3 Haowen Gu,1 Bo Liu,3,5 Kun Bao1,3,4,6 1Second Clinical Medical College, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 2The Affiliated TCM Hospital of Guangzhou Medical University, Guangzhou, People's Republic of China; 3State Key Laboratory of Dampness Syndrome of Chinese Medicine, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine (Guangdong Provincial Hospital of Chinese Medicine), Guangzhou, People's Republic of China; 4Guangdong-Hong Kong-Macau Joint Laboratory on Chinese Medicine and Immune Disease Research, Guangzhou, People's Republic of China; 5Guangzhou Key Laboratory of Chirality Research on Active Components of Traditional Chinese Medicine, Guangzhou, People's Republic of China; 6Guangdong Provincial Key Laboratory of Chinese Medicine for Prevention and Treatment of Refractory Chronic Disease, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine (Guangdong Provincial Hospital of Chinese Medicine), Guangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Bo Liu; Kun Bao, Email doctliu@gzucm.edu.cn; baokun@aliyun.comBackground: Nephrotic syndrome (NS) and its numerous complications remain the leading causes of morbidity and mortality globally. Sanqi Qushi granule (SQG) is clinically effective in NS. However, its potential mechanisms have yet to be elucidated.Methods: A network pharmacology approach was employed in this study. Based on oral bioavailability and drug-likeness, potential active ingredients were picked out. After acquiring overlapping targets for drug genes and disease-related genes, a component-target-disease network and protein-protein interaction analysis (PPI) were constructed using Cytoscape, followed by GO and KEGG enrichment analyses. Adriamycin was injected into adult male Sprague-Dawley (SD) rats via the tail vein to establish NS model. Kidney histology, 24-hr urinary protein level, creatinine (Cr), blood urea nitrogen (BUN), triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL-C) level were assessed. Western blotting, immunohistochemistry, and TUNEL staining were applied.Results: In total, 144 latent targets in SQG acting on NS were screened by a network pharmacology study, containing AKT, Bax, and Bcl-2. KEGG enrichment analysis suggested that PI3K/AKT pathway was enriched primarily. In vivo validation results revealed that SQG intervention ameliorated urine protein level and podocyte lesions in the NS model. Moreover, SQG therapy significantly inhibited renal cells apoptosis and decreased the ratio of Bax/Bcl-2 protein expression. Moreover, we found that Caspase-3 regulated the PI3K/AKT pathway in NS rats, which mediated the anti-apoptosis effect.Conclusion: By combining network pharmacology with experimental verification in vivo, this work confirmed the treatment efficacy of SQG for NS. SQG protected podocyte from injury and inhibited kidney apoptosis in NS rats via the PI3K/AKT pathway at least partially.Keywords: Sanqi Qushi granule, nephrotic syndrome, podocyte injury, kidney apoptosis, network pharmacology, PI3K/AKT pathway